CULTURAL RELATIONS BETWEEN THE REPUBLIC OF UZBEKISTAN AND THE KINGDOM OF SAUDI ARABIA: THE CASE OF THE “SHARQ TARONALARI” FESTIVAL - Rustamboev Islomjon Doniyor ugli (International Journal of Literature and Language Studies, 2026)
This article analyzes the role and significance of the International Music Festival “Sharq Taronalari” in the development of cultural relations between the Republic of Uzbekistan and the Kingdom of Saudi Arabia. The study examines the history of the festival’s establishment, its stages of international development, and the dynamics of the growing number of participating countries and delegates from a scholarly perspective. It also analyzes the participation of representatives of the Kingdom of Saudi Arabia in the festival, their contribution to the promotion of national musical heritage, as well as the processes of cultural diplomacy and intercultural dialogue fostered between the two states through the festival. The findings of the research demonstrate that the “Sharq Taronalari” festival is one of the important instruments of Uzbekistan’s international cultural policy and plays a significant role in strengthening cultural cooperation with Saudi Arabia.